Designing Pictures Story Book Using Cultural Language Learning Approach (CLLA) to Improve English Skills - Nurul Fatma; Sujito (Presscience, 2025)
This study aimed to develop a Picture Story Book (PSB) to enhance English proficiency among elementary learners and to identify appropriate teaching materials. The research employed a Research and Development (R&D) approach, structured using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observations, interviews, and questionnaires during the needs analysis phase. The English material, titled